Data Management Plan: Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) - Tobon, Hector; Thornton, Philip K.; Smit, Wiebe (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
This global data management plan’s primary purpose is to help AICCRA support evidence-based decision-making by ensuring that the research data, which is essential for the integrity, quality, and value of research, is appropriately managed at the project level. It also strengthens the culture of results-based project monitoring and evaluation (M&E) by ensuring the reporting of high-quality information products. AICCRA will make these information products available for the long-term to partners and the scientific community following an Open Access Policy. The CGIAR and the Alliance of Bioversity International and CIAT also recommend the implementation of FAIR (Findable, Accessible, Interoperable, and Reusable) principles for each output.